Class-Based Philosophy as the Leading Cause of Education Crisis - G. G., Zhubangalieva (2020)
These days everyone agrees that school and the whole educational system is in the middle of the crisis, although the attempts taken to reform it are still underway in the form of modernization and updating of educational content, changing the evaluation system, implementing the digital technologies, etc. Every effort directed towards this goal is focused on elaboration of class-based school and lection-seminar university systems that are the main varieties of group learning, which was established in 15th-16th centuries to allow mass character of education. The organizational framework of group learning consists of three educational forms: individual, in-pair and in-group.In-group form is the prevailing one and exists in two modification - whole-class (frontal) work and small-group work (historically: teamwork).